Changing the perceptions and attitudes of rural Ghanaian youth towards cocoa farming. Issue 7 (3rd October 2022) - Kodom, Michael; Azumah, Shaibu Baanni; Boateng, Nathaniel Amoh; Tsekpo, Emile Mawutor; Mensah, Kwadwo Boadi; Boateng, Ethel
ABSTRACT: Cocoa farmers in Ghana are aging, and this threatens the sustainability of the sector. Using a qualitative approach, this study assessed how the youth-centred training programme has changed existing negative perceptions on youth participation in cocoa farming. The results confirmed that youth disinterest in cocoa farming is partly influenced by the perception that cocoa farming is an activity for the aged. The positive effect of applying the knowledge and skills beneficiaries received in enhancing the quality of cocoa farms and improving cocoa yield have changed existing negative public perceptions. Youth-centred interventions inspire hope in the revitalisation of Ghana's cocoa sector.